2015
DOI: 10.1016/j.ccell.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Retinoids in IKZF1-Mutated BCR-ABL1 Acute Lymphoblastic Leukemia

Abstract: SUMMARY Alterations of IKZF1, encoding the lymphoid transcription factor IKAROS, are a hallmark of high risk acute lymphoblastic leukemia (ALL), however the role of IKZF1 alterations in ALL pathogenesis is poorly understood. Here we show that in mouse models of BCR-ABL1 leukemia, Ikzf1 and Arf alterations synergistically promote the development of an aggressive lymphoid leukemia. Ikzf1 alterations result in acquisition of stem cell-like features, including self-renewal and increased bone marrow stromal adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
178
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(205 citation statements)
references
References 52 publications
14
178
0
3
Order By: Relevance
“…After B-cell lineage specification, IKAROS is again required for the orderly transition through the highly proliferative pre-B-cell stage. Here the importance of IKAROS is underscored by the consequence of reduction in IKAROS activity, which arrests pre-B cells in a premalignant state that can progress to B-ALL that is refractory to anti-leukemic therapy (Joshi et al 2014;Churchman et al 2015). Our current investigation into the molecular mechanisms by which IKAROS controls this critical phase in B-cell precursor differentiation sets a new paradigm for regulation of lineage progression and fidelity that is based on simultaneous positive and negative regulation of superenhancer networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After B-cell lineage specification, IKAROS is again required for the orderly transition through the highly proliferative pre-B-cell stage. Here the importance of IKAROS is underscored by the consequence of reduction in IKAROS activity, which arrests pre-B cells in a premalignant state that can progress to B-ALL that is refractory to anti-leukemic therapy (Joshi et al 2014;Churchman et al 2015). Our current investigation into the molecular mechanisms by which IKAROS controls this critical phase in B-cell precursor differentiation sets a new paradigm for regulation of lineage progression and fidelity that is based on simultaneous positive and negative regulation of superenhancer networks.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of these genes was also examined in leukemic cells generated by transformation of primary IKDN pre-B cells by the oncogenic tyrosine kinase BCR-ABL1 (Roumiantsev et al 2001). These leukemic cells retain the "neuro-epithelial" gene signature and epithelial cell-like phenotypes of primary IKDN pre-B cells (Churchman et al 2015; N Jena, I Joshi, T Yoshida, Z Zhang, Z Liu, P Tata, A Raufi, IM Shapiro, D Weever, JA Pachter, et al, unpubl.). Expression of Tead1/2, Hoxb5, Hoxb6, Hoxb7, and Hoxb8 was increased further in IKDN BCR-ABL1 + leukemic pre-B cells, while the level of native B-cell transcription factors such as Ebf1 was not significantly changed (Fig.…”
Section: Ikaros Represses a Transcriptional Network Of Nonlymphoid Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it remains unclear whether and how these factors impact Ikzf1 expression. Studies in leukemic pre-B cells have shown that retinoids up-regulate Ikzf1 expression and imply a role for the retinoic acid receptor family in IKAROS gene regulation and leukemia treatment (Churchman et al 2015).…”
Section: Expression and Immune Cell Phenotypesmentioning
confidence: 99%
“…Moreover, preclinical efficacy of retinoids in IKZF1-mutated BCR-ABL1 cell lines and patient-derived xenograft models have been recently described. 36 IKZF1 alterations drive stem cell renewal, cause abnormal bone marrow adhesion, and result in decreased TKI sensitivity. Retinoids have been shown to reverse this phenotype and potentiate TKI activity in IKZF1-altered mouse and human BCR-ABL1 ALL.…”
mentioning
confidence: 99%